Literasi Hukum Generasi Z Tertib Berlalu Lintas dan Dokumen Kependudukan Siswa Kelas XII SMA Negeri 1 Pemalang - Idayanti, Soesi; Widyastuti, Tiyas Vika; Indriasari, Evy; Aryani, Fajar Dian; Hamzani, Achmad Irwan (Nawadeepa: Jurnal Pengabdian Masyarakat, 2024)
Improving the legal literacy of Generation Z (Gen-Z) especially among the students of the twelfth grade of Higher State High School, is essential to equip them with the knowledge necessary to live in an increasingly complex and globally connected society. Gen-Z is facing a variety of problems in the traffic and specific documentation of the current. The main problems are non-compliance with traffic rules, restricted understanding of traffic regulations, high mobility, less popular use of public transport, reliance on navigation applications can cause drivers to pay less attention to signs and changes in road conditions. Related documents include a lack of understanding of the importance of documents such as a ID card, family card, or birth certificate. Technology and data security challenges where technological advances can bring challenges related to data security and potential risks of population data hacking, restricted access to population services. Improving legal literacy for Gen-Z in Higher State High Schools 1 Advocates require an innovative, holistic, and tailored approach to the characteristics and needs of students. Through effective and inclusive education, Gen- Z, Class XII students of High State High school 1 advocates can better understand their rights and responsibilities in the legal community, including improved understanding of traffic rules and occupation documents, adequate regulation, violation of administrative processes that facilitate access to Gen Z occupation papers and the use of technology to enhance safety and driving awareness among Gen-Z.